Islamization of science: Ziauddin sardar's critique of the universality of science - Putawa, Rilliandi Arindra (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Introduction: Science, which initially emerged due to the awareness of the need for Islamic values' influence on the development of knowledge, in Sardar's perspective, becomes a critique of the universality of science. This underscores the need for further research regarding Sardar's concept of Islamic Science as a critique of the universality of knowledge. Methods: This qualitative research explores Ziauddin Sardar's critique of Western-influenced universal science. It employs a literature study to analyze Sardar's thoughts using various methods. Finding: The findings reveal that Islamic science, rooted in ethical principles, offers an alternative to Western science, which often overlooks diverse paradigms and local knowledge systems. While Islamic science excels in addressing region-specific issues, it may struggle with complex problems. In contrast, Western science, considered global, has historically caused environmental challenges by disregarding non-conventional paradigms. Therefore, Islamic science, with its inclusive approach to knowledge, presents a potential solution to the crises stemming from the dominance of Western scientific paradigms. Conclusion: Islamic science is a comprehensive paradigm, similar to Western science, that can serve as a framework for scientists from various fields of knowledge. The Islamic paradigm attempts to critique the concept of universality, which has been one of the values embraced by the Western scientific paradigm. This concept has been one of the reasons why scientific revolutions have occurred slowly.